LEGAL PRINCIPLES OF THE MECHANISM FOR PROTECTING HUMAN AND CITIZEN RIGHTS AND FREEDOMS - Boyko, Oleg (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: to conduct a study of the legal principles of the mechanism for ensuring human rights and freedoms. Research methods: analysis, synthesis, systematization, generalization, comparison. Results: the essence of the mechanism for ensuring rights and freedoms was clarified - it is a system of guarantees established by the relevant state authorities and non-state institutions, which are defined in national legislation and international standards, the legal principles were determined: the rule of law, legality, equality, humanism, legal certainty, good faith, proportionality. Special attention was paid to the legal principles of the mechanism for protecting human and citizen rights as a result of the introduction of the legal regime of martial law in Ukraine, large-scale war and mass violations of human rights. Discussion: in conditions of a full-scale war, it is important to adhere to the above-mentioned legal principles of the mechanism for ensuring the rights of citizens, and the quality and efficiency of the activities of both state authorities and the non-state sector must be increased. In Ukraine, there is a system of bodies and officials at various levels that protect the rights and freedoms of man and citizen: the President of Ukraine, the Verkhovna Rada of Ukraine, local state administrations, a system of courts of general jurisdiction and specialized courts, the Constitutional Court of Ukraine, the Commissioner of the Verkhovna Rada of Ukraine for Human Rights, the prosecutor’s office, the bar, notaries, etc. Further development of ensuring the rights and freedoms of citizens is inextricably linked with improving the quality and efficiency of the entire system of state bodies and non-state institutions, which must adhere to the above-mentioned legal principles in their activities.